Synthesis, antioxidant capacity and aggregation of carotenoid-curcumin conjugates and hybrids - Santiago Jijón; Dalma Czett; Katalin Böddi; Gergely Gulyás-Fekete; Veronika Nagy; Anikó Takátsy; György T. Balogh; József Deli; Attila Agócs (PLoS ONE, 2026)
Both curcumin and carotenoids are good antioxidants and curcumin has a pleiotropic effect additionally. To combine the beneficial properties carotenoid succinates were coupled to curcumin via ester bond. In another approach hemicurcumin was condensed with apocarotenoid aldehydes to produce a hybrid of the carotenoid and the curcuminoid part. Antioxidant activity of these products was determined with the ABTS-TEAC method in ethanol and in isotonic phosphate buffer saline. Covalent coupling of 8’-apo-β-carotenol, β-cryptoxanthin, capsanthin, and lutein to curcumin via succinate ester significantly increased the antioxidant capacity compared to the parent carotenoids or carotenoid succinates. Derivatization of zeaxanthin, nevertheless, did not improve its properties. The direct merging of hemicurcumin with apocarotenals resulted in extended conjugated polyenes with higher antioxidant activities, that, however, seems to be more effected by the number of phenolic moieties than by the number of conjugated double bonds. The open-chain carotenoid end-group can also contribute to a better antioxidant activity. The lipophilic conjugates and hybrids showed aggregation in aqueous media, thus the determined TEAC values in PBS rather characterize the aggregates than the individual molecules. Based on the drug-prediction studies and TEAC values, bisphenolic hybrids of curcumin with 12,12’-diapo-dialdehyde and crocetindial have the best characteristics for being drug candidates, but an appropriate delivery system is necessary.